Working a second job: Cell adhesion proteins that moonlight in the nucleus - Haage, Amanda; Dhasarathy, Archana (Frontiers in Cell and Developmental Biology, 2023)
Cells are adept at sensing changes in their environment, transmitting signals internally to coordinate responses to external stimuli, and thereby influencing adaptive changes in cell states and behavior. Often, this response involves modulation of gene expression in the nucleus, which is seen largely as a physically separated process from the rest of the cell. Mechanosensing, whereby a cell senses physical stimuli, and integrates and converts these inputs into downstream responses including signaling cascades and gene regulatory changes, involves the participation of several macromolecular structures. Of note, the extracellular matrix (ECM) and its constituent macromolecules comprise an essential part of the cellular microenvironment, allowing cells to interact with each other, and providing both structural and biochemical stimuli sensed by adhesion transmembrane receptors. This highway of information between the ECM, cell adhesion proteins, and the cytoskeleton regulates cellular behavior, the disruption of which results in disease. Emerging evidence suggests a more direct role for some of these adhesion proteins in chromatin structure and gene regulation, RNA maturation and other non-canonical functions. While many of these discoveries were previously limited to observations of cytoplasmic-nuclear transport, recent advances in microscopy, and biochemical, proteomic and genomic technologies have begun to significantly enhance our understanding of the impact of nuclear localization of these proteins. This review will briefly cover known cell adhesion proteins that migrate to the nucleus, and their downstream functions. We will outline recent advances in this very exciting yet still emerging field, with impact ranging from basic biology to disease states like cancer.